String Quartets [de Wolfgang Amadeus Mozart] = Streichquartette [von Wolfgang Amadeus Mozart] = Les quatuors à cordes [de Wolfgang Amadeus Mozart] = Quartetti per archi [di Wolfgang Amadeus Mozart] - Mozart, Wolfgang Amadeus ((Complete Mozart Edition ;)
Contiene: 1) Quartet Nº 1 in G, KV 80/73f; 2) Quartet Nº 2 in D, KV 155/134a ; 3) Quartet Nº 3 in G, KV 156/134b ; 4) Quartet Nº 4 in C, KV 157 ; 5) Quartet Nº 5 in F, KV 158 ; 6) Quartet Nº 6 in B Flat, KV 159 ; 7) Quartet Nº 7 in E Flat, KV 160/159a ; 8) Quartet Nº 8 in F, KV 168 ; 9) Quartet Nº 9 in A, KV 169 ; 10) Quartet Nº 10 in C, KV 170 ; 11) Quartet Nº 11 in E Flat, KV 171 ; 12) Quartet Nº 12 in B Flat, KV 172 ; 13) Quartet Nº 12 in D Minor, KV 173 ; 14-19) The Six Haydn Quartets (Nº 14-19) ; 20) Quartet Nº 20 in D, KV 499, Hoffmeiter ; 21-23) The Three Prussian Quartets (Nº 21-23).